Variable coefficient control of a wave-energy device - Young, Henry Eskine; Pollock, J. (The University of Edinburgh, 1985)
In 1979 Mynett, Serman and Mei produced a set of com-puter programmes which allowed the prediction of the hydrodynamic performance of an arbitrary shape on lin-ear assumptions. Using their programs Greenhow simu-lated the behaviour of ducks on compliant mountings and came up with the conclusion that any shape could produce nearly 100% in a narrow tank provided that all three axes were properly controlled and that condi-tions remained linear. At the same time work was being done in Edinburgh to explore the effects of power extraction from the model mounting using heave and surge damping in addition to heave and surge spring. It was also necessary to consider the effects of torque and force limits dictated by economic and structural requirements and this non-linearity took the problem beyond anything that could be handled by the theoretical workers. The combinatorial explosion of variables made experiments very tedious and led to the approach described in this paper.
Keywords: Edinburgh Wave Power Project; Duck; Control; Tank testing